2013
DOI: 10.3109/10408444.2013.842956
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological evaluation of proteins introduced into food crops

Abstract: This manuscript focuses on the toxicological evaluation of proteins introduced into GM crops to impart desired traits. In many cases, introduced proteins can be shown to have a history of safe use. Where modifications have been made to proteins, experience has shown that it is highly unlikely that modification of amino acid sequences can make a non-toxic protein toxic. Moreover, if the modified protein still retains its biological function, and this function is found in related proteins that have a history of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 100 publications
1
74
0
2
Order By: Relevance
“…Prior to making any GM crops, all potential proteins that would be produced by the inserted gene (called a "transgene") are screened using computer algorithms to ensure that they are not similar to known allergens, toxins, antinutritional proteins, disease agents, or pharmacologically active proteins (Delaney et al, 2008;Silvanovich et al, 2009;Hammond et al, 2013). For example, comparing candidate proteins to known allergens is typically done using sequence alignment programs, such as BLAST or FASTA, and by using a so-called sliding eight-amino-acid window search.…”
Section: Breeding Of Gm Crops Sources Of Candidate Genes For Gm Cropsmentioning
confidence: 99%
“…Prior to making any GM crops, all potential proteins that would be produced by the inserted gene (called a "transgene") are screened using computer algorithms to ensure that they are not similar to known allergens, toxins, antinutritional proteins, disease agents, or pharmacologically active proteins (Delaney et al, 2008;Silvanovich et al, 2009;Hammond et al, 2013). For example, comparing candidate proteins to known allergens is typically done using sequence alignment programs, such as BLAST or FASTA, and by using a so-called sliding eight-amino-acid window search.…”
Section: Breeding Of Gm Crops Sources Of Candidate Genes For Gm Cropsmentioning
confidence: 99%
“…The CP4 EPSPS proteins are enzymes acting on the shikimic acid pathway for the biosynthesis of aromatic amino acids in plants, showing high substrate specificity. The two insecticidal proteins (Cry1A.105 and Cry2Ab2) act through cellular receptors found in target insect species, and it is reported that the gastrointestinal tract of mammals, including humans, lacks receptors with high specific affinity to Cry proteins (Hammond et al, 2013;Koch et al, 2015).…”
Section: Toxicologymentioning
confidence: 99%
“…A key element of the safety evaluation for introduced proteins in GM crops is a bioinformatic analysis to assess whether the introduced protein shows similarity to known toxins or allergens (Hammond et al, 2013;Kier and Petrick, 2008). Bioinformatics analyses were performed on the translated sequence of the DMO coding sequence in these three DT crops to assess their structural relatedness with known allergens and toxins.…”
Section: Bioinformatics Analyses Of Potential Allergenicity and Toxicmentioning
confidence: 99%
“…The guidance for assessing the safety of proteins introduced into a GM crop has been developed and harmonized for more than 20 years (Delaney et al, 2008;Hammond et al, 2013;Herouet et al, 2005;Kier and Petrick, 2008). A weight of evidence approach to protein safety is founded on risk assessment principles that include data from both hazard identification studies and exposure assessments.…”
Section: Introductionmentioning
confidence: 99%